Wavelength-interval-switchable multi-wavelength thulium-doped fiber laser with a nonlinear dual-pass Mach-Zehnder interferometer filter in 2-μm-band. (January 2022) - Guo, Ying; Yan, Fengping; Feng, Ting; Qin, Qi; Bai, Zhuoya; Li, Ting; Han, Wenguo; Zhou, Hong; Suo, Yuping
Highlights: A wavelength-interval-switchable MWTDFL based on a NDP-MZI filter is proposed and demonstrated. Two 20-wavelength operations are obtained and switched between each other flexibly. The maximum power/wavelength fluctuation of 20-wavelength operation are 0.612 dB/0.04 nm. 60 lasing wavelengths within a 3-dB bandwidth are obtained by adjusting the PCs. Abstract: A wavelength-interval-switchable multi-wavelength thulium-doped fiber laser (MWTDFL) is proposed and demonstrated, based on a nonlinear dual-pass Mach-Zehnder interferometer (NDP-MZI) filter for the first time. We investigate the NDP-MZI filter theoretically and experimentally, which has both the transmission characteristics of a dual-pass Mach-Zehnder interferometer (DP-MZI) for wavelength selection and a nonlinear optical loop mirror (NOLM) for suppressing wavelength competition. By tuning two polarization controllers (PCs), two 20-wavelength operations with an opposite phase and a same wavelength-interval of 0.46 nm are obtained and switched between each other flexibly. The maximum power fluctuation and wavelength drift measured are 0.612 dB and 0.04 nm, respectively. In addition, due to the power-equalizing effect resulting from the NOLM, 60 lasing wavelengths within a 3-dB bandwidth with an adjacent wavelength-interval of 0.23 nm are also obtained by adjusting the PCs carefully, and the stability of the MWTDFL is measured experimentally. Furthermore, the performance of the NDP-MZI using an 80 m highly nonlinear fiber has been studied in detail as well. The proposed MWTDFL may find great applications in optical communication and optical sensing.